2018
DOI: 10.1159/000490108
|View full text |Cite
|
Sign up to set email alerts
|

Fournier’s Gangrene: Literature Review and Clinical Cases

Abstract: Background: Fornier gangrene is an extremely rare disease of the genitals. This disease is a result of the urogenital tract, anorectal area, and genital skin infections, appearing usually in immunocompromised patients with diabetes, obesity, and malignant neoplasms. The basic treatment of Fournier gangrene includes an emergency surgical intervention combined with antibiotic therapy and detoxification. Methods: A review of recent papers comprising studies and reviews published in 2005–2016 was performed. The cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
24

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(153 citation statements)
references
References 14 publications
(15 reference statements)
2
108
0
24
Order By: Relevance
“…Fournier's gangrene is known to be a rapid onset disease, but studies have shown that application to the hospital is delayed by an average of one week after initial symptoms have presented. [13] In our study, the median time from symptom onset to hospital application was four (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) days. Immediate diagnosis and treatment of FG are known to affect prognosis.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Fournier's gangrene is known to be a rapid onset disease, but studies have shown that application to the hospital is delayed by an average of one week after initial symptoms have presented. [13] In our study, the median time from symptom onset to hospital application was four (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) days. Immediate diagnosis and treatment of FG are known to affect prognosis.…”
Section: Discussionmentioning
confidence: 62%
“…The age of the patients hospitalized in the intensive care unit (ICU) was found to be higher than the patients who did not require ICU admittance (65.33±11.63 years vs. 54.39±11.79 years, respectively; p=0.013). Median FGSI score was 2 (0-14), while the median UFGSI score was 4 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Median FGSI and UFGSI scores were found to be higher in patients accepted to the ICU compared to those who were not (4 vs. 2, p=0.025; and 6 vs. 3, p=0.002, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Ulug et al [16] and Luján Marco et al [13] did not find any significant association between the day of presentation to the hospital and mortality. Chernyadyev et al [32] also noted that manifestations of venereal diseases should be differentiated from the initial features of FG so as to prevent development of fulminant disease.…”
Section: Discussionmentioning
confidence: 99%